Contralateral intraocular pressure lowering effect of prostaglandin analogues - Rao, Harsha L. (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Though the use of prostaglandin analogues (PGA) for reduction of intraocular pressure (IOP) has shown a marked increase, studies evaluating the contralateral effects of PGA are limited. AIMS: To evaluate if PGA treatment in one eye has an effect on the IOP of the untreated fellow eye. DESIGN: Retrospective study. MATERIALS AND METHODS: Thirty patients of open-angle glaucoma with no previous antiglaucoma treatment underwent 24-hour diurnal IOP phasing. They subsequently were started on a uniocular trial with PGA, and had office diurnal IOP measurements 6 weeks later. Twenty-four hour diurnal consisted of 8 IOP readings over 24 hours and office diurnal consisted of 4 IOP readings between 8 AM and 6 PM at 3 hourly intervals. STATISTICAL ANALYSIS: IOPs of the fellow eye during the office diurnal were compared with IOPs at similar time points during the 24-hour diurnal using paired t-tests. RESULTS: Mean (± standard deviation) IOP in the treated eye reduced (P < 0.001) from 17.17 ± 3.2 mm Hg at baseline to 13.7 ± 2.4 mm Hg at 6 weeks, while that in the untreated eye reduced from 16.4 ± 3.1 mm Hg to 14.8 ± 2.7 mm Hg (P = 0.01). The decrease in IOP in the untreated fellow eye was statistically significant at 8 AM (2.7 mm Hg, P = 0.003) and 11 AM (2.3 mm Hg, P = 0.01) but not so at 2 PM (1.2 mm Hg, P = 0.10) and 5 PM (0.9 mm Hg, P = 0.19). The amount of IOP reduction in the untreated eye was significantly associated with the magnitude of IOP reduction in the treated eye (β = 0.69, P = 0.008). CONCLUSION: Uniocular PGA treatment tends to reduce the IOP of the untreated fellow eye.